THE EFFECT OF SLOPE DAMAGE DUE TO BLASTING ON THE SLOPE STABILITY - Chairianti Ahmad, Isti
Mining activities have various impacts on the surrounding environment. One of the impact is rock fatigue that is caused by repeated loading. That problem can lead to rock damage and cause slope failure of the minesite. One of the mining activities that is counted as repeated loading is blasting activities. According to the test that is conducted by Safitri (2019), repeated loading dynamically affects the change in rock strength. Repeated loading by using impact tests affects the value of the UCS and the Young Modulus value of the rock. The more collisions is given, the value of UCS and the Modulus Young is smaller. The results of the test can be used to estimate the changes of rock strength due to the influence of slope damage from blasting activities. In addition, damage due to blasting also affects the stability of the slope. Therefore, a research is needed to know the effect of slope damage due to blasting on the change of rock strength and slope stability. The research is conducted by using a calculation method based on Hoek & Brown failure criteria and modeling for the analysis of slope stability with the Bishop Simplified method. The research is started by making blasting design. From the design, the pressure and the stress of the blasting result are obtained. The required data to estimate the characteristics of rock mass is obtained from the research data of Safitri (2019). Rock characteristics are calculated by using a calculation method based on Hoek & Brown failure criteria in two conditions, before and after blasting. Cohesion value and deep friction angle in slope condition before blasting or before damage existing (D = 0) is 0.088 Mpa and 38.36 °, the value of cohesion and deep friction angle in slope condition after blasting damage (D = 0.013) is 0.087 Mpa and 38.26 ° , and the value of cohesion and deep friction angle in condition where the rock is destroyed (D = 1) is 0.03 Mpa and 22.07 °. Then, the research is continued with analyzing the stability of the slope on model design by using the Rocscience Slide 6.0 program with the Bishop Simplified method. The result of this research is the damage due to blasting is 0.0127 with a range of effect about 1.99 meters and the damage due to blasing is 1 with range of effect about 1.53 meters. The decrease of rock mass strength due to the blasting damage causes a decrease of slope stability. The safety factor on the slope condition before damage existing is 2.450, and the safety factor on the slope after damage existing due to blasting is 1.345. Both numbers of those safety factors shows a stable condition of the slope.